Gold Mining and Proto-Urbanization : Recent Evidence from Ghana - Fafchamps, Marcel (Oxford University Press, 2016)
Central place theory predicts that agglomeration can arise from external shocks. We investigate whether gold mining is a catalyst for early stages of urbanization in rural Ghana. We call this phenomenon proto-urbanization. Using cross-sectional data, we find that locations with gold mines exhibit most of the tell-tale signs of proto-urbanization. They have higher population densities, and they are also sites where more sophisticated forms of economic activity agglomerate. These findings are consistent with agglomeration effects that induce non-farm activities to coalesce in a particular location. Over time, we find that an increase in gold production is associated with more specialization, but not with a clear sectoral transformation of employment. We also find that the changes arising from increasing gold production are not reversed when large gold mines shrink. Rather, they continue to become more consistent with processes of structural transformation.